Transient Left Ventricular Apical Ballooning in a Postmenopausal Woman with Chronic Liver Disease, Malignancy, and Recent Ischemic Stroke: A Case Report and Review of the Literature. (25th November 2012) - Covell, Dustin; Clendenen, Nathan
Abstract : Transient left ventricular apical ballooning (TLVAB), or Takotsubo cardiomyopathy, is a poorly understood phenomenon that is thought to be related to a surge of catecholamines under stress conditions that causes microvascular dysfunction and a unique pattern of myocardial stunning. TLVAB occurs in two distinct patient populations: (i) community presentation similar to acute coronary syndrome and (ii) the critically ill. Understanding the differences in presentation, prognosis and management between these two groups may improve the outcome. We present a case of TLVAB developing in a Caucasian postmenopausal female who developed TLVAB suddenly on a background of chronic liver disease, malignancy, and recent ischemic stroke. The patient presented with hemodynamic collapse and was treated with inotropes, vasopressors, and supportive care until cardiac function improved. Additionally, we review the current literature describing the risk factors, pathophysiology, and treatment of TLVAB.